Triaxial rotor plus particle description of negative-parity states in 125Xe - Lieberz, D.; Gelberg, A.; Granderath, A.; von Brentano, P.; Ragnarsson, I.; Semmes, P. B. (Nuclear Physics, Section A, 1991)
Excitation energies and branching ratios in 125Xe have been correctly described by using the triaxial rotor plus particle model with deformation parameter ε{lunate}=0.25 and γ=24°. The observed properties, in particular the degeneracy of the yrast favoured and unfavored bands and the signature inversion in the yrare bands are well described by the model. The distribution of core states in the wave functions has been calculated. This distribution has been used in interpreting the signature inversion and the staggering in B(E2) and B(M1) which have been predicted by the model.